FC071: An HDAC Inhibitor Attenuates Crescentic Glomerulonephritis and Avoid Chronic Kidney Disease Enhancing Podocyte Progenitor Differentiation. (3rd May 2022) - Elena Melica, Maria; Antonelli, Giulia; Semeraro, Roberto; Lucia Angelotti, Maria; De Chiara, Letizia; Conte, Carolina; Lugli, Gianmarco; Julie Peired, Anna; La Regina, Gilda; Mazzinghi, Benedetta; Lazzeri, Elena; Lasagni, Laura; et al.
Abstract: BACKGROUND AND AIMS: Crescentic glomerulonephritis (crescentic GN) encompasses a group of diverse disorders characterized by the presence of massive hyperplasia of parietal epithelial cells (PEC) as the main histopathological lesion at kidney biopsy. It is associated with a rapid decline in kidney function. Typically, crescent formation is the consequence of diverse upstream pathomechanisms involving the specific activation of PEC. PEC normally reside peacefully along Bowman capsule and represent in part renal progenitor cells (RPC). Previous studies observed RPC markers in crescents from patients with different types of glomerulonephritis. Similarities between stem cell niches of bone marrow and kidney, prompted us to hypothesized that crescents result from monoclonal expansion of a single RPC clone conceptually similar to monoclonal diseases originating from hematopoietic stem cells. According to this analogy, we further hypothesized that drugs known to cure monoclonal disease of the hematopoietic stem cells by enforcing their terminal differentiation could also attenuate crescentic glomerulonephritis. METHOD: To address this hypothesis, we established a crescentic GN disease model in a conditional transgenic mouse based on the mT/mG and the Confetti reporter that allows lineage tracing and clonal analysis of RPCs. Animals were treated with known pharmacological inhibitors of clonal stem cell proliferation in myeloproliferative disorders. Crescentic lesions were characterized by super-resolution STED microscopy. Finally, we employed single cell RNA sequencing of human renal progenitor cultures to identify the immature progenitor subset-generating crescent in human to identify putative new biomarkers of crescentic GN to validate in biopsy of patients. RESULTS: We observed that the crescentic lesions originated from the clonal expansion of single RPC, thus suggesting a clonal stem cell disorder. Therefore, we administrated a series of drugs known to ameliorates myeloproliferative neoplasms to our crescentic GN mouse model as potential therapeutic agents. Treatment with one of the compounds induced a reduction in both proteinuria and crescent formation. STED super-resolution imaging of glomeruli showed that this compound turned the uncontrolled hyperplasia of a specific immature PEC subset into a controlled differentiation into podocytes thereby restoring the injured glomerular filtration barrier. Moreover, delayed drug administration still induced proteinuria remission and avoided long-term development of chronic kidney disease (CKD), an effect associated to a continued generation of new podocytes and crescent regression over time. Single cell RNA sequencing of human RPC identified a new marker of the crescent-generating progenitor cells. Expression of this marker in biopsies of patients with crescentic GN associated with progression toward end stage kidney disease. Treatment of human PEC with the drug that in in vivo experiments showed a therapeutic effect on crescentic GN reduced proliferation of the immature progenitor subset promoting their differentiation into podocytes. CONCLUSION: These results demonstrate that glomerular hyperplastic lesions derive from clonal amplification of a RPC subset and that shifting proliferation to podocyte differentiation reverses improves clinical outcome and avoid CKD.